Studi Hermeneutika Teks Mazmur 42 dan Implikasinya untuk Pemulihan Mandiri dari Depresi dengan Melakukan Komunikasi Intrapersonal - Jekson Tulus; Sang Putra Immanuel Duha; Lilis Haryanti; Markus Tuhumury (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2024)
Man's fall into sin resulted in the human soul being vulnerable and fragile. If not addressed immediately, it will cause social problems. Returning something to its original condition is the goal of restoration. Not only God, individual participation is the main key to turning things around. Instead of demanding that circumstances change, what is more important is to change your personal perspective in dealing with problems, and that is personal responsibility. This process is called self-healing. By using intrapersonal communication methods, an individual is able to become the best healer for himself. Reflecting on the experience of a psalmist in Psalm 42, psychological values are implied that can be applied in today's life to reduce psychological illnesses, such as depression. Through an exegetical approach and integrating it with psychology, a coping mechanism can be formulated that can help believers to carry out self-healing, as first aid.